Mindfulness and Leadership: Communication as a Behavioral Correlate of Leader Mindfulness and Its Effect on Follower Satisfaction - Arendt, Johannes F. W.; Pircher Verdorfer, Armin; Kugler, Katharina G. (Frontiers in Psychology, 2019)
In recent years, the construct of mindfulness has gained growing attention in psychological research. However, little is known about the effects of mindfulness on interpersonal interactions and social relationships at work. Addressing this gap, the purpose of this study was to investigate the role of mindfulness in leader-follower-relationships. Building on prior research, we hypothesize that leaders’ mindfulness is reflected in a specific communication style (“mindfulness in communication”), which is positively related to followers’ satisfaction with their leaders. We used nested survey data from 34 leaders and 98 followers from various organizations and tested mediation hypotheses using hierarchical linear modeling. Our hypotheses were confirmed by our data. Leaders’ self-reported mindfulness showed a positive relationship with several aspects of followers’ satisfaction. This relationship was fully mediated by leaders’ mindfulness in communication as perceived by their followers. Our findings emphasize the potential value of mindfulness in workplace settings. They provide empirical evidence for a positive link between leaders’ dispositional mindfulness and the wellbeing of their followers, indicating that mindfulness is not solely an individual resource but also fosters interpersonal skills. By examining leaders’ mindfulness in communication as an explanatory process, we created additional clarification about how leaders’ mindfulness relates to followers’ perceptions. Moreover, by suggesting mindfulness in communication as a behavioral correlate of mindfulness, we offered a promising starting point for indirect measures of mindfulness.